On ∗-representations of deformations of canonical anticommutation relations - Proskurin, D. P.; Sukretnyi, K. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider irreducible ∗-representations of deformations of canonical anticommutation relations (CAR) that belong to the class of ∗-algebras generated by generalized quons.